1992
DOI: 10.1128/jvi.66.12.7303-7308.1992
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus open reading frame 61 protein is functionally homologous to herpes simplex virus type 1 ICP0

Abstract: The varicella-zoster virus (VZV) open reading frame 61 (ORF61) protein is thought to be the homolog of herpes simplex virus type 1 (HSV-1) ICPO, based on gene location and limited amino acid homology. However, HSV-1 ICPO trans activates HSV-1 genes, while VZV ORF61 protein trans represses the function of VZV trans activators on VZV promoters in transient expression assays. To investigate the functional relatedness of HSV-1 ICPO and VZV ORF61 protein, we established Vero and MeWo cell lines which stably express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…The fact that this factor has to be expressed before it can perform its activities corresponds with the time course of JNK/SAPK and p38/MAPK phosphorylation described here and recently [Rahaus et al, 2004]. Moriuchi et al [1992] demonstrated a reduction of viral replication when a MeWo cell line expressing VZV ORF61 was infected with HSV strain KOS. Our data demonstrate that the VZV replication is also repressed in MeWo/61 cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The fact that this factor has to be expressed before it can perform its activities corresponds with the time course of JNK/SAPK and p38/MAPK phosphorylation described here and recently [Rahaus et al, 2004]. Moriuchi et al [1992] demonstrated a reduction of viral replication when a MeWo cell line expressing VZV ORF61 was infected with HSV strain KOS. Our data demonstrate that the VZV replication is also repressed in MeWo/61 cells.…”
Section: Discussionsupporting
confidence: 76%
“…VZV deleted in ORF 61 is impaired for replication in vivo, but can be complemented [Cohen and Nguyen, 1998]. Due to its homologies to HSV ICP0, VZV ORF61 is also able to complement a herpes simplex-virus type 1 (HSV-1) ICP0 mutant [Moriuchi et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…Northern blot analysis was performed as described previously (32). Probes specific to the CXCR4 or glyceraldehyde-3-phosphate dehydrogenase gene were prepared as described previously (29).…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…ORF61 encodes a 62-to 66-kDa phosphoprotein (45), which is highly homologous to herpes simplex virus 1 (HSV-1) ICP0 in the RING finger domain and can partially complement the function of ICP0 in ICP0-null HSV-1 (28). Both proteins exhibit regulatory functions, but the difference between them is that ORF61 has either a transactivated or repressive function (16,31), while ICP0 mostly shows transcriptional activation (12,14).…”
mentioning
confidence: 99%